2009
DOI: 10.1007/s11103-009-9523-9
|View full text |Cite
|
Sign up to set email alerts
|

The first crystal structures of a family 19 class IV chitinase: the enzyme from Norway spruce

Abstract: Chitinases help plants defend themselves against fungal attack, and play roles in other processes, including development. The catalytic modules of most plant chitinases belong to glycoside hydrolase family 19. We report here x-ray structures of such a module from a Norway spruce enzyme, the first for any family 19 class IV chitinase. The bi-lobed structure has a wide cleft lined by conserved residues; the most interesting for catalysis are Glu113, the proton donor, and Glu122, believed to be a general base tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…CHI4 has been demonstrated to have antifungal effects (Ubhayasekera et al, 2009) and has been indicated to mediate programmed cell death (PCD) during embryogenesis in Norway spruce (Wiweger et al, 2003). Mediation of PCD by CHI4 presumably occurs through action on endogenous arabinogalactan proteins or lipo-chitooligosaccharides (Wiweger et al, 2003), conceptually releasing oligosaccharides with signaling properties (Fossdal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CHI4 has been demonstrated to have antifungal effects (Ubhayasekera et al, 2009) and has been indicated to mediate programmed cell death (PCD) during embryogenesis in Norway spruce (Wiweger et al, 2003). Mediation of PCD by CHI4 presumably occurs through action on endogenous arabinogalactan proteins or lipo-chitooligosaccharides (Wiweger et al, 2003), conceptually releasing oligosaccharides with signaling properties (Fossdal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the two lobes in the RSC-c•(GlcNAc) 4 complex are opened (green). Such opened conformations are frequently observed in unliganded forms of the GH19 chitinases [18]. Based on these conformational differences, Ubhayasekera et al [18] suggested that the binding of the substrate to the enzyme brings the two lobes close to each other in order to place the catalytic residues in optimal conformations for catalysis, forming a competent structure for the hydrolysis reaction.…”
Section: Activity and Mode Of Action Of W72a Rsc-cmentioning
confidence: 99%
“…On the other hand, a GH19 chitinase lacking the loops except Loop III (''loopless'' chitinases) was isolated from moss, Bryum coronatum [11]. Based on the amino acid sequence alignment, the structure of the moss enzyme is closely related to those of GH19 chitinases from Streptomyces griseus HUT6037 [12], Streptomyces coelicolor A3(2) [13], and Norway spruce [14]. Thus, the structural organization of the GH19 enzymes was intensively studied, and the structural data have been accumulated.…”
Section: Introductionmentioning
confidence: 99%